PEMBERDAYAAN MASYARAKAT DALAM MENUNJANG GIZI SEIMBANG SUKU ANAK DALAM DESA BUKIT SUBAN - Asparian, Asparian; Fitri, Ridhatul; Anjani, Putri Surya; Munawarah, Ratu Atikah; Yunanda, Fina Ayu; Humayroh, Nasywa (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2024)
Purpose: Community empowerment through organic fertilizer technology by the GEMPITA KAT ORMAWA PPK Jambi University 2024 Team in Bukit Suban Village aims to increase horticultural productivity and nutrition of Suku Anak Dalam children. Methodology: The empowerment is carried out in the living area of the Suku Anak Dalam community in SAD Bukit Suban Village, Air Hitam District, Sarolangun Regency. The approach method used to solve the problems in the Suku Anak Dalam (SAD) of Bukit Suban Village is (1) program planning and preparation, (2) program implementation, (3) monitoring and evaluation. Results: Jambi University's PPK ORMAWA GEMPITA KAT team designed a community nutrition program in Suku Anak Dalam Bukit Suban Village. The program includes organic fertilizer technology training, land clearing, fertilizer production, planting, maintenance, kale harvesting, and cooking together to improve the community's balanced diet. The limitations of this study include limited coverage of the Suku Anak Dalam community in Bukit Suban Village, reliance on community participation, a short study period, and the influence of external factors such as climate and soil conditions that are not fully controlled. The contributions of this research are beneficial in several areas, include : community empowerment, sustainable agriculture, nutrition and public health, social development, education and training. Conclusion: The organic farming potential of Bukit Suban Village has not been optimized, causing nutritional problems in Suku Anak Dalam. Jambi University's PPK ORMAWA GEMPITA KAT team designed an organic fertilizer program to improve nutrition and community welfare.